Formulation of carbon black-ionomer dispersions for thin film formation in fuel cells - Hoffmann, Eva-Maria; Zhang, Su; Thoma, Martin; Damm, Cornelia; Peukert, Wolfgang (Particuology, 2019)
The performance of proton exchange membrane fuel cells (PEMFC) is strongly determined by the structure and composition of the electrode layer. The interactions between the ionomer, carbon black particles, and solvent affect the suspension properties and thus the layer morphology. We analyze the effect of the ionomer-to-carbon (I/C) weight ratio for two different types of carbon black on the suspension and layer characteristics. Highly branched carbon blacks with a high surface area tend to form less cracked layers. As less branched carbons can pack together more closely, a smaller pore size results in a larger capillary pressure during drying and thus more cracks. The added ionomer adsorbs on the carbon particles and improves the colloidal stability of the carbon black particles. The carbon black aggregates are thus smaller, resulting in closer packing and thinner layers. Moreover, the addition of the ionomer increases the critical coating thickness (CCT) of the layers because drying stresses are dissipated by the deformation of the ionomer, preventing crack formation. An optimum I/C weight ratio is identified for optimal layer formation and minimized crack formation.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Carbon black; Cracking; Layer formation; Perfluorosulfonic acid (PFSA) ionomer; Porosity

Impact of DAA/water composition on PFSA ionomer conformation. - Hoffmann, Eva-Maria; Fischer, Daniela; Thoma, Martin; Damm, Cornelia; Lobaz, Volodymyr; Zhigunov, Alexander; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2020)
Performance of a proton exchange membrane fuel cell (PEMFC) is significantly determined by the structure and composition of the electrode layer. Electrode layers are formed from inks consisting of platinum-doped carbon black particles, perfluorosulfonic acid (PFSA) ionomer and a dispersing solvent. Interaction between these materials mainly influences suspension stability, ionomer conformation and therewith layer morphology. We characterize the interplay between a short sidechain (SSC) PFSA ionomer (Aquivion® D79-25BS) and a solvent mixture (diacetone alcohol (DAA) and water with different weight ratios) by using Hansen solubility/dispersibility parameters (HSP) and by experimental tests. It was found that HSPs are well suitable to describe the ionomer/solvent interactions. In particular, the HSP difference in terms of the hydrogen bonds is responsible for the poor affinity between ionomer and solvent at low DAA concentrations. With increasing DAA content the affinity between ionomer and solvent increases as indicated by better matching HSPs. For an ionomer concentration of 4 wt%, Aquivion always forms molecular solutions for all DAA-in-water mixing ratios. Self-organization of the ionomer molecules changes from densely packed/collapsed molecules with highly deprotonated sulfonic acid side groups at low DAA concentrations to unfolded Aquivion molecules with a low dissociation degree of the sulfonic acid groups at high DAA concentrations.

Ionomer and protein size analysis by analytical ultracentrifugation and electrospray scanning mobility particle sizer - Wawra, Simon; Thoma, Martin; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Damm, Cornelia; Peukert, Wolfgang (European Biophysics Journal, 2018)
Keywords: Analytical ultracentrifugation; Scanning mobility particle sizer; Combined analysis; Multiwavelength detector

n-Hexanol Enhances the Cetyltrimethylammonium Bromide Stabilization of Small Gold Nanoparticles and Promotes the Growth of Gold Nanorods - Schmutzler, Tilo; Schindler, Torben; Zech, Tobias; Lages, Sebastian; Thoma, Martin; Appavou, Marie-Sousai; Peukert, Wolfgang; Spiecker, Erdmann; Unruh, Tobias (ACS Applied Nano Materials, 2019)
Gold nanorods (AuNRs) are of interest for many applications, since their absorption in the regime of visible light can easily be tuned by their exact shape. To produce these AuNRs, a two-step synthesis that starts from small seed particles is used. These seed particles are stabilized by cetyltrimethyl-ammonium bromide (CTAB), which forms micelles at the used concentration (0.1 mol/L). In this work, the influence of the micelle morphology on the stabilization of these seed particles and the consequences on the formation of AuNRs is reported. The elongation of CTAB micelles by the addition of n-hexanol leads to much more stable seed particle dispersions and thus less polydisperse AuNRs. In contrast, a higher number of micelles compared to pure CTAB dispersions result from the addition of n-pentanol. This promotes the formation of larger seed particles and leads to lower yields of AuNRs. The gold nanoparticles are characterized by UV-vis-NIR absorption spectroscopy, transmission electron microscopy, and small-angle X-ray scattering (SAXS). The morphology of the micelles has been determined by a combination of SAXS and small-angle neutron scattering (SANS). The experimental results were used to calculate the collision kinetics of seed particles by using an improved approach of classical coagulation theory to consider the anisotropy of the micelles. The combination of these experiments with the calculations strongly supports the mechanistic model-that these gold seed particles are not stabilized by a CTAB bilayer but by the micelles itself. For the first time, the influence of the micellar size and shape on the stabilization mechanism of noble metal nanoparticles could be clarified. Theses findings contribute to the development of targeted design routes for distinct nanoparticle morphologies by the use of suitable dispersions.
CRIS-Team WoS Importer:2019-06-18

Simple and Reliable Method for Studying the Adsorption Behavior of Aquivion lonomers on Carbon Black Surfaces - Damm, Cornelia; Thoma, Martin; Hoffmann, Eva-Maria; Sattes, Maria-Melanie; Segets, Doris; Peukert, Wolfgang; Lin, Wei (Langmuir, 2018)
A better understanding of the interactions of carbon black and perfluorinated sulfonic acid (PFSA) ionomer helps to improve the effectiveness of polymer electrolyte membrane fuel cells. We present a simple and fast method for quantitative PFSA ionomer analysis based on suspension density measurements. After validation of the reliability of our method by thermogravimetric analysis and isothermal titration calorimetry (ITC), we investigate the adsorption equilibrium of short-side-chain PFSA ionomers of different equivalent weights (EW) and polarities on carbon black. The measured adsorption isotherms exhibit a plateau in the ionomer surface concentration for ionomer equilibrium concentrations <= 2 g/L. In this concentration range, the adsorption isotherms are described by the Langmuir model, whereby the surface concentrations in the plateau region are between 0.041 and 0.070 g/g. The plateau value of the ionomer surface concentration increases with EW and therefore with decreasing number of side chains with terminal sulfonic acid group per ionomer molecule, while the amount of adsorbed sulfonic acid groups remains constant for all investigated ionomers, resulting in similar zeta-potentials and sedimentation stability of the suspensions. The free energies of adsorption Delta G calculated from the association constants of the adsorption isotherms agree well with Delta G values obtained by isothermal titration calorimetry (ITC) and thus validate the adsorption isotherm measurement method. From the values of adsorption enthalpy Delta H ((-7.3 +/- 0.8) kJ/mol) and entropy Delta S (ca. 100 J/(mol K)), which were extracted from ITC, we conclude that the ionomer adsorption on carbon black is a spontaneous physisorption process.
Keywords: nano; carbon; allotrope; black